2019
DOI: 10.3389/fimmu.2019.02820
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enriched T Cell Epitope Specificity in Full T Cell Receptor Sequence Repertoires

Abstract: High-throughput T cell receptor (TCR) sequencing allows the characterization of an individual's TCR repertoire and directly queries their immune state. However, it remains a non-trivial task to couple these sequenced TCRs to their antigenic targets. In this paper, we present a novel strategy to annotate full TCR sequence repertoires with their epitope specificities. The strategy is based on a machine learning algorithm to learn the TCR patterns common to the recognition of a specific epitope. These results are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
167
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 31 publications
2
167
0
Order By: Relevance
“…Previous work has tackled this problem from an epitopespecific angle, and demonstrated that the amino acid sequences of the TCR CDR3 region contain sufficient information to predict epitope recognition using epitope-specific models (10,11,14,(16)(17)(18). These types of predictive models have now been made accessible to immunology researchers via web tools such as TCRex (19). One shortcoming of an epitope-specific approach is that a unique model needs to be trained for every epitope (or for a set of epitopes in the case of Bi et al (17)), which requires sufficient training examples of TCRs with the same epitope specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has tackled this problem from an epitopespecific angle, and demonstrated that the amino acid sequences of the TCR CDR3 region contain sufficient information to predict epitope recognition using epitope-specific models (10,11,14,(16)(17)(18). These types of predictive models have now been made accessible to immunology researchers via web tools such as TCRex (19). One shortcoming of an epitope-specific approach is that a unique model needs to be trained for every epitope (or for a set of epitopes in the case of Bi et al (17)), which requires sufficient training examples of TCRs with the same epitope specificity.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting work that brings peptide–TCR recognition to the same side is that of Gielis et al, who identified epitope-specific TCR sequences using a random forest algorithm [ 213 ]. However, it can only predict TCR sequences based on the peptides present in the training database.…”
Section: Prediction Of T Cell Epitopesmentioning
confidence: 99%
“…Though their focus is more on immunogenicity of peptides presented to MHC molecules, they also observed correlation between individual TCR-pMHC affinities and the features important for immunogenicity score. Gielis et al [77] applied random forest-based classifiers for epitope specific TCRs to repertoire level analysis. Their models successfully detected the increase of epitope specific TCRs upon vaccination in two Yellow Fever vaccination studies.…”
Section: Epitope Specificitymentioning
confidence: 99%